THE IMPACT OF INTERMITTENT FASTING ON COGNITIVE FUNCTION AND INFLAMMATORY MARKERS IN MIDDLE-AGED AND OLDER ADULTS: A COMPREHENSIVE SYSTEMATIC REVIEW AND META-ANALYSIS - Loganathan, Yaasheni; Chin Yi Ying; Meramat, Asheila (Malaysian Journal of Public Health Medicine, 2026)
Intermittent fasting (IF) has shown potential health benefits, including improved glucose homeostasis, stress resistance, and reduced inflammation, as well as slowing cognitive decline. However, studies focusing on older adults have been limited and often contradictory. This systematic review and meta-analysis aim to comprehensively examine the impact of IF on cognitive function and inflammatory markers in middle-aged and older adults. The meta-analysis showed that IF significantly enhances cognitive function, as measured by the Mini-Mental State Examination (MMSE). These results suggest that while IF can enhance cognitive function, it is ineffective in reducing inflammatory markers. Nevertheless, an association was found between IF, cognitive function, and inflammation. Recommendations for future work include larger randomized controlled trials to confirm the cognitive benefits of IF and mechanistic studies to clarify its effects on inflammatory markers.